PERANCANGAN BANDAR UDARA DENGAN PENDEKATAN POSTMODERN - Firdhani, Rio Anantha; Siswadi, Rony Setya; Widati, Titiani (Fakultas Teknik Universitas Palangka Raya, 2025)
Haji Muhammad Sidik Airport in Barito Utara plays a crucial role as an air transportation hub and a catalyst for regional development. Based on 2024 data, the airport served 20,750 passengers, while future projections estimate an increase of up to 90,000 passengers annually. The existing terminal is therefore considered inadequate to accommodate this growth, necessitating a redesign that responds to capacity and comfort challenges. This study proposes a passenger terminal design using a Postmodern architectural approach with the substyle of Post Capital Sustainability. This approach emphasizes ecological and spiritual sustainability through the integration of passive design strategies, local materials, and a deep connection to the landscape and local culture. The design process is directly guided by the principles of Post Capital Sustainability and is carried out through literature review, precedent study, comparative analysis, site observation, and user needs assessment. The results show that design strategies such as natural ventilation (stack effect), daylight optimization, the use of local materials, and a gable roof form aligned with the Barito River flow enhance thermal comfort and contextual aesthetics. This approach offers an alternative airport architectural model that is not only efficient and responsive to tropical climates, but also reflects local values in a more humanistic and sustainable manner.